Analisis Kekerasan Verbal dalam Program Indonesia’s Next Top Model Cycle 2 - Triadnyani, Cantika; Suryawati, I Gusti Agung Alit; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2024)
Indonesia's Next Top Model Cycle 2 is a reality show program with an R13+ rating and aired during prime time, but this program has verbal violence in it. This study aims to describe the verbal violence displayed in Indonesia's Next Top Model Cycle 2. This qualitative research using John Fiske's semiotic analysis focuses on episodes 1, 32, and 38. Based on the results of the research, the dominant verbal violence seen is 1) cursing with harsh expressions/yelling with a high tone of voice, 2) insulting/mocking, 3) demonizing someone behind, and 4) humiliating/cornering in front of others. At the level of reality, verbal violence is seen in dialog, expressions, and the environment. Verbal violence is also highlighted in the aspects of camera, sound, editing, and lighting. Furthermore, individualism is seen as an ideology of the way to winning and self-defense in competition. Keywords: John Fiske Semiotic Analysis, Verbal Violence, Reality Show